The Understanding and Purchase Decision of Environmentally Friendly Products Based on Gender - ., Suryawati; Zahra, E Lutfia; ., Cholilawati (KnE Social Sciences, 2020)
The paid plastic bag policy is an effort to train the community to help lessen the use of plastic and switch to different products such as cardboard or recycled packaging bags as some mini markets do. Those who do not consider environmentally friendly products describe that they are people who do not understand the environment. The purpose of this research is wanting obtain information on the knowledge of products environmentally friendly on gender (male / female) of the decision the purchase. The study is done in jakarta and its surroundings.In this study, sample divided into categories consumers consumers men and women, employees and manager location, the number of members sample each category at least 30. The research method used in this study is mixed methods. The target population in this study is a minimarket that has run a paid plastic program in Jakarta. Analysis of the data used in this study uses two approaches, namely, a qualitative approach and a quantitative approach. The results of this study indicate that there is no difference between understanding and purchasing decisions that men and women have regarding environmentally friendly products. Keywords: environment understanding, purchase decision, gender, green products